RESTING ECOLOGY AND SPATIAL HETEROGENEITY OF FILARIASIS MOSQUITO VECTORS IN TROPICAL WETLANDS: IMPLICATIONS FOR INTEGRATED VECTOR CONTROL IN BANYUASIN, INDONESIA - Rini Pratiwi; Peni Kusumasari; Fitriyanti (Jurnal Kedokteran dan Kesehatan : Publikasi Ilmiah Fakultas Kedokteran Universitas Sriwijaya, 2026)
Lymphatic filariasis remains a public health challenge in tropical wetland ecosystems, where mosquito resting ecology is still poorly understood despite its importance for vector survival and control effectiveness. This study analyzed resting behavior, species composition, and spatial heterogeneity across four endemic villages in Banyuasin, Indonesia. A total of 2,752 mosquitoes representing 26 species were collected, dominated by Mansonia uniformis, Culex tritaeniorhynchus, Culex vishnui, and Mansonia annulifera, accounting for over 70% of individuals. Spatial patterns revealed that vegetation-rich wetlands favored Mansonia, while agricultural landscapes supported Culex species. Most dominant species exhibited exophilic resting behavior, whereas Culex quinquefasciatus showed more endophilic tendencies. Peak resting activity occurred between 19:00 and 22:00. Although no infective filarial larvae were detected, the high abundance of competent vectors suggests continued transmission potential. These findings highlight the importance of integrating resting ecology and landscape heterogeneity into comprehensive vector surveillance and control strategies.